PENGARUH CAPITAL ADEQUCAY RATIO, LOAN TO DEPOSIT RATIO DAN PERBANDINGAN BIAYA OPERASIONAL DENGAN PENDAPATAN OPERASIONALTERHADAP RETURN ON ASSET PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - I Made Suidarma (Majalah Ilmiah Widyacakra, 2019)
A banking institution can be determined by its profitability, namely, ability to make profit from certain capital, so it can be more efficient. Bank performance can be determined from several indicator. One of main indicators to become basic judgment is related bank financial performance, it can be seen from financial report. Total sample used is 29 banking firms that fulfill sample criteria. Data type used is primary data analyzed using double linier regression analysis, t-test and f-test. Analysis result obtained value t count variable Capital Adequacy Ratio as 3,199 with significance value 0,002 < 0,05 means there is positive and significance effect variable Capital Adequacy Ratio to Return On Asset. Value t count for variable Loan to Deposit Ratio as 2,313 with significance value 0,023 < 0,05 means there is positive and significance effect variable Loan to Depost Ratio toward Return On Asset. Value t count for variable Operational Revenue operational Cost as -8,028 with significance value 0,000 < 0,05 means there is negative and significance effect variable Operational Revenue Operational Cost toward Return On Asset. Value F count as 43,481 with significance value as 0,000 < 0,05, means that there is significance effect simultaneously between Capital Adequacy Ratio, Loan To Deposit Ratio, Operational Revenue Operational Cost toward Return On Asset